(untitled) (Research Announcements "Heritage BG", 2025)
The article discusses for the first time in a comparative perspective the interpretation of the Conversion of the Bulgarians in the commentaries to the hagiographies of chosensaints fromthe firstvolumes of the Baroque hagiographic series Acta Sanctorum. The author defines the work of the Bollandists in the context of the first attempts to reconstruct the history of the Church made by Matthias Flacius Illyricus and Cesar Baronius. The paper outlines the progress made in studying the sources for the conversion of the Bulgarians through textual-critical methods, which have made it possible to reconstruct a reliable historical narrative and a generally justifiable chronology of events in the initial stage of humanities research in Europe. References: Andreeva, N. (2004). Pokarastvaneto na balgarite v nemski piesi ot XVIII–XIX v. Veliko Tarnovo. Bozhilov, I. (2017). Istoria na srednovekovna Balgaria. T. 1. Varvarska Balgaria. Sofia. Gjuzelev, V. (2006). Pokrastvane i hristiyanizatsia na balgarite. Sofia. Nikolov, A. (1992). Balgarskata tema v Analite na Baronij. In: Katolicheskata duhovna kultura i nejnoto prisastvie i vliyanie v Balgaria. Sofia, 115–122. Vlaevska, A. (2010). Obrazat na knyaz Boris-Mihail v katolicheskata istoriografia IX–XVII v. (ot Reginon, abat na Pryum, do kardinal Tsezar Baroniy) – Fundamenta Europaea, 5, 47-64. Vlaevska, A. (2011). Fortuna di un racconto: la Conversione di Boris, Re dei Bulgari. – Ricerche Slavistiche, 9 (55) 2011, 223-237. Zaimova, R. (1988). Nyakoi italianski avtori ot XV v. za balgarskata istoria. In: Sbornik Bulgaria, Italia i Balkanite. Obshtestveno-istoricheski i kulturno-esteticheski vzaimootnoshenia, XV–XX v. Sofia, 68-78. Zaimova, R. (1992). Balgarskata tema v zapadnoevropeyskata knizhnina, XV–XVII vek. Sofia. Zaimova, R. (2011). Han /kan/ Tervel – mezhdu traditsiyata i modernostta. In: Balkanite. Modernizatsia, identichnosti, idei. Sbornik v chest na 70-god. na prof. Nadya Danova. Sofia, 616–635. Berkoff, G. B. (1988/1989). The History of Christian Rus’ in the ‘Annales Ecclesiastici’ of Caesar Baronius, Harvard Ukrainian Studies, Vol. 12/13, 551-575. Conte, G. B. (1996). The Rhetoric of Imitation: Genre and Poetic Memory in Virgil and Other Latin Poets. Ed. Cjarles Seagal. Ithaca and London. Petavius, D. (1636). Rationarium temporum, in partes duas, libros decem tributum, in quo aetatum omnium sacra profanaque historia chronologicis probationibus munita summatim traditur. Parisiis: Sumptibus S. Cramoisy. Picchio, R. (1986). La Bulgaria nella storia ecclesiaetica del Baronie. In: Per Valdo Zilli. (Annali del Dipartimento di Studi dell’Europa Orientale (Napoli). Sezione storico-sociale, 4-5, 1982-1983), Roma, 41-52. Pullapilly, C. K. (1975). Caesar Baronius. Counter-reformation Historian. Notre Dame, Indiana.